Sikap Profesional Dan Loyalitas Kerja Perawat Di Masa Pandemi Covid-19 - Diana Rachmania; Widyasih Sunaringtyas (HEALTH CARE: JURNAL KESEHATAN, 2023)
ABSTRACT The condition of the COVID-9 pandemic is a formidable challenge for nurses where nurses have a high risk of contracting COVID-19. Nurses keep going to work, completing their duties in caring for patients responsibly as a form of high nurse work loyalty. On the other hand, nurses also have a professional obligation to care for patients in various conditions, including during the COVID-19 pandemic. This study was to determine the relationship between professional attitude and work loyalty of nurses during the COVID-19 pandemic. The research design was correlational with a cross sectional approach. The population was 48 nurses and with the total sampling technique, a sample of 48 respondents is obtained. The independent variable was professional attitude and the dependent variable was nurse job loyalty. Measuring tool using a questionnaire from each variable. Data were analyzed by Spearman's rho test with Î± <0.05. The results showed that most of the respondents (69%) had a good professional attitude and most of the respondents (77.1%) had high work loyalty. The results of the Spearman rho test show that the p value is 0.000 with r = 0.702, which means that there was a relationship between professional attitude and work loyalty of nurses during the COVID-19 pandemic. Nurses are expected to be able to carry out professionalism and have good work loyalty in carrying out nursing care to patients so that they can provide quality services. Keywords: professionalism, work loyalty, nurse, the COVID-19 pandemic